A Remark on the Characterization of the Global Behavior of a Process with Independent Increments - Zcikusilo О. K. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We show that the analysis of the global behavior of a process with independent increments in terms of the existence of the stationary distribution of the corresponding storage process leads to results that differ from the classical ones.